Effect of Diet and Dietary Components on the Composition of the Gut Microbiota - Beam, Ashley; Clinger, Elizabeth; Hao, Lei (Nutrients, 2021)
Diet and dietary components have profound effects on the composition of the gut microbiota and are among the most important contributors to the alteration in bacterial flora. This review examines the effects the “Western”, “plant-based”, “high-fat”, “medical ketogenic”, and “Mediterranean” diets have on the composition of the gut microbiota in both mice and human subjects. We show that specific dietary components that are commonly found in the “plant-based” and “Mediterranean” diet play a role in shifting the microbial composition. This review further evaluates the bacterial metabolites that are associated with diet, and their role in systemic inflammation and metabolic endotoxemia. Furthermore, the associations between diet/dietary components and altering bacterial composition, may lead to potential therapeutic targets for type II diabetes, obesity, and inflammatory diseases.